Drug-drug interactions between tyrosine kinase inhibitors and concomitance medications: Drug safety in cancer treatment - Nam, Trinh Ho; Thanh, Le Van; Huong, Nguyen Thi Thu; Tien, Thai Thi My; Han, Tran Thi Ngoc; Thanh, Trinh Thi; Anh, Nguyen Thi Kim (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Background: Tyrosine kinase inhibitors are increasingly used in the treatment of cancer. Drug interactions involving tyrosine kinase inhibitors are commonly encountered in clinical practice. Objectives: To analyze DDI between TKIs and the concomitant medication. Materials and Methods: Retrospective observational study carried out at Cho Ray hospital’s oncology center. We evaluated the data of patients who were prescribed tyrosine kinase inhibitor from January 2023 to August 2023. Medication data were extracted from electronic medical records. Drug Interaction Checker (Drugs.com) and MicroMedex Drug Interaction (MM) were utilized to identify potential interactions between tyrosine kinase inhibitors and concomitant medications. Interactions were then assessed by the investigators for clinical significance. The main outcome was the frequency of significant drug interactions involving tyrosine kinase inhibitors and concomitant medications. Secondary outcomes included describing the nature and clinical impact of interactions and describing interactions by medication class. Results: A total of 250 patient files were included for analysis, in which 232 interactions were screened. 140 potential interactions were identified by Micromedex software, with 139 (49.1%) considered “major”. Interaction Checker (Drugs.com) detected 73 (25.8%) potential interactions classified as “major” and 159 (74.1%) as “moderate” level of interaction. Potential clinical consequences included QTc prolongation, decreased tyrosine kinase inhibitor concentrations, and increased concentration of concurrently used drugs due to tyrosine kinase being inhibitors of CYP3A4. Conclusions: Drug interactions in prescriptions for TKIs are common in clinical practice. Therefore, physicians prescribing TKI should be careful of this phenomenon. Short-acting agents should be preferred for gastric acid suppression because PPIs alter the bioavailability of several TKIs. Prolongation of QT, which is also a major effect of TKIs drug interactions, is a life-threatening consequence. Oncology pharmacists should play a role in screening for tyrosine kinase inhibitor-linked interactions, recommending alternative drugs or dose timing strategies, and monitoring concurrently used drugs toxicity.